High-performance self-powered NO2 sensor based on nitrogen-doped MOF derived indium oxide core-shell fiber structure and preparation method of high-performance self-powered NO2 sensor
Through the combination of the In2O3 core-shell fiber structure derived from nitrogen-doped MOF and friction nanogenerator, the existing NO2 sensors have solved the problem of slow response and recovery time, insufficient sensitivity and dependence on traditional power supplies at room temperature, achieving high performance and low Power consumption and self-powered NO2 detection.
Patent Information
- Application Number
- CN202411608839.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
The existing NO2 sensors based on metal oxide semiconductors have slow response and recovery time at room temperature, their sensitivity needs to be improved, and relying on traditional power supplies, it is difficult to achieve low power consumption and self-power supply.
The In2O3 core-shell fiber structure derived from nitrogen-doped MOF is used as a sensitive material, and is prepared by hydrothermal method and annealing treatment, and combined with a friction nanogenerator to achieve self-power supply. The porous fibrous core-shell structure and nitrogen doping properties of this structure enhance the adsorption and charge transfer capabilities of NO2.
The detection of NO2 is achieved with high sensitivity and low detection lower limit (100ppb) at room temperature, with significantly improved response value, shortened response time, and realized self-powered function, reducing dependence on traditional power supplies.
Smart Images

Figure CN119413857A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor metal oxide gas sensors, and specifically relates to a high-performance self-powered NO2 sensor based on a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material and a preparation method thereof. Background Art
[0002] Nitrogen dioxide (NO2) is a ubiquitous environmental pollutant that poses a major threat to health, especially to vulnerable groups such as patients with asthma, hypertension, and coronary heart disease. Therefore, high-sensitivity NO2 detection at room temperature using portable devices is essential for disease diagnosis and public health management.
[0003] Metal oxide semiconductor (MOS) nanomaterials, such as In2O3, WO3, SnO2 and ZnO, are commonly used gas-sensing materials due to their simple preparation, good stability and high sensitivity. Among them, In2O3 has unique advantages such as wide band gap (3.55-3.75 eV), low resistivity (1 kΩ-160 kΩ) and higher conductivity (conductivity exceeds 1000 S / m), and has been proven to be an ideal NO2 gas sensor material. However, the response and recovery time of MOS-based gas sensors at room temperature are often slow, and the sensitivity needs to be improved. These problems can be solved by changing the microstructure and surface properties of In2O3. Metal organic frameworks (MOFs) have become a feasible solution, which have special surface areas, tunable structures and adjustable porosity to enhance gas adsorption and sensitivity. Rationally designed MOF derivatives can retain the excellent microstructure and surface active state characteristics of MOF, thereby obtaining excellent gas sensing performance. Studies have shown that electron-rich n-carbon residues can provide electrons to oxides, improving conductivity and detection sensitivity. In addition, the exploration of sensor morphology modulation helps to improve the sensing performance of the sensor. The core-shell structure enhances the accessibility of the pores and promotes gas diffusion, while maintaining a unique design that ensures strong interactions between the core and shell, resulting in a synergistic effect. On this basis, the rational design of MOF-derived In2O3 sensitive materials can simultaneously adjust the adsorption and conductivity capabilities, thereby achieving high-performance NO2 detection at room temperature.
[0004] In addition, with the development of the Internet of Things (IoT), the new generation of gas sensors requires low power consumption and high selectivity to ensure potential applications in wireless sensor platforms and smart gas monitoring. It is also crucial to integrate lightweight and sustainable power sources into the sensors. Triboelectric nanogenerators provide a promising method to convert mechanical energy from the surrounding environment into electrical energy, promoting the development of self-powered nitrogen dioxide sensors and eliminating the dependence on traditional power sources (NanoEnergy, 2012, 1, 328-334). Summary of the invention
[0005] The purpose of the present invention is to provide a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material and a preparation method thereof.
[0006] The NO2 sensor involved in the present invention uses a nitrogen-doped MOF-derived In2O3 core-shell fiber structure (N-MOF-In2O3) as a sensitive material, and obtains nitrogen-doped MOF-In2O3 by a simple hydrothermal method, annealing treatment, and subsequent NO2 gas exposure strategy. On the one hand, nitrogen doping is activated by exposing the planar device to NO2, which is beneficial to the reconstruction of the surface electronic state and the transfer of charge; on the other hand, the unique porous fibrous core-shell structure of In2O3 derived from nitrogen-doped MOF promotes NO2 molecules to be more easily adsorbed on the surface of the material. In addition to having high sensitivity at room temperature, the sensor obtained by the present invention also has a low detection limit (100 ppb) and good selectivity. The response value of the sensor based on N-MOF-In2O3 to 1 ppm NO2 at room temperature is 1460, which is 93 times that of commercial In2O3. At room temperature, sensitive detection of NO2 gas as low as 100 ppb can be achieved. The unique porous fibrous core-shell structure, effective nitrogen doping, and the resulting reconstruction of surface electronic states enhance the NO2 adsorption and charge transfer capabilities, resulting in excellent NO2 sensing performance at room temperature.
[0007] In addition, a self-powered flexible NO2 room temperature sensor was obtained by integrating the nitrogen-doped MOF-derived In2O3 (N-MOF-In2O3) flexible gas sensor with a friction nanogenerator composed of a thermoplastic polyurethane film doped with multi-walled carbon nanotubes and a polytetrafluoroethylene film.
[0008] The present invention discloses a high-performance self-powered NO2 sensor based on a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material, such as Figure 1As shown, it consists of two parts: a friction nanogenerator and a flexible NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material. The friction nanogenerator is composed of polyethylene terephthalate (PET) film, copper foil, multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film, modified polytetrafluoroethylene (PTFE) film, copper foil, and polyethylene terephthalate (PET) film from bottom to top, and the polyethylene terephthalate (PET) film on both sides plays a supporting role. Copper foil is used as the upper and lower electrodes (size is 4 cm × 3 cm), polytetrafluoroethylene (PTFE) film is used as the negative friction material, and the surface roughness is improved by modification with sandpaper; multi-walled carbon nanotubes with a conductive network are introduced into thermoplastic polyurethane (TPU) to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film as a positive friction material; the flexible NO2 sensor is prepared by coating a suspension of MOF-derived In2O3 core-shell fiber structure sensitive material on a polyimide (PI) substrate (8-12mm × 8-12mm) with gold (Au) interdigitated electrodes (12 to 18 pairs, with a spacing of 40 to 60μm between each pair of electrodes) on the surface, and then exposing it to 3 to 8ppm NO2 for 1 to 3 hours, wherein the preparation steps of the MOF-derived In2O3 core-shell fiber structure sensitive material are as follows:
[0009] (1) Dissolve 0.50-0.65 g In(NO3)3·4.5H2O and 0.20-0.30 g terephthalic acid in 15-25 mL dimethylformamide (DMF) solution and stir for 25-35 min to obtain a uniform solution;
[0010] (2) adding the uniform solution obtained in step (1) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing the autoclave well and maintaining the autoclave at 110 to 140° C. for 3 to 7 hours;
[0011] (3) After the autoclave is naturally cooled to room temperature, the reaction product is taken out, the precipitate is collected by centrifugation, and the precipitate is washed alternately with water and ethanol for 5 to 8 times, and the obtained precipitate is dried at 70 to 90°C for 10 to 20 hours to obtain a solid powder, and the obtained solid powder is calcined in air at 400 to 600°C for 1.5 to 3.0 hours (heating rate 3.0 to 6.0°C / min), thereby obtaining a MOF-derived In2O3 core-shell fiber structure sensitive material.
[0012] The method for preparing a NO2 gas sensor based on a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material according to the present invention comprises the following steps:
[0013] (1) 10-20 mg of MOF-derived In2O3 core-shell fiber structure sensitive material was placed in an agate mortar, 150-200 μl of ethanol was added, the mixture was fully mixed and ground into a paste; the paste was then dipped and evenly coated on a polyimide (PI) substrate with a gold (Au) interdigitated electrode on the surface to form a 15-30 μm thick sensitive material layer, and the sensitive material layer completely covered the surface of the polyimide (PI) substrate and the gold (Au) interdigitated electrode;
[0014] (2) The PI substrate coated with the sensitive material obtained in step (1) is dried in air at 60 to 80° C. for 1.5 to 3.0 hours, thereby preparing a planar flexible NO2 gas sensor of MOF-derived In2O3 core-shell fiber structure sensitive material.
[0015] (3) Exposing the MOF-derived In2O3 core-shell fiber structure sensitive material in step (2) to 3-8 ppm NO2 for 1-3 hours to obtain a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3), thereby preparing a planar flexible NO2 gas sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material.
[0016] The method for preparing a triboelectric nanogenerator (MTP-TENG) based on a modified polytetrafluoroethylene (PTFE) film and a multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film according to the present invention comprises the following steps:
[0017] (1) Preparation of multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film: 6-9 g of thermoplastic polyurethane (TPU) particles are added to 40 mL of dimethylformamide (DMF) solution, followed by adding 0.5-1.5 g of multi-walled carbon nanotubes (MWCNT), and the mixture is kept at 60-80° C. for 10-15 hours; 23-35 g of sodium chloride (NaCl) is then added, and the mixture is kept at 60-80° C. for 5-8 hours; the resulting product is then dried at 60-80° C. for 3-6 hours, and then dissolved in 50-70° C. water for 0.5-1.5 hours to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) as a positive friction material, and then placed in a polytetrafluoroethylene mold and dried to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film with a thickness of 2-5 mm;
[0018] (2) Preparation of modified polytetrafluoroethylene (PTFE) film: using P1000 grade sandpaper to uniformly rub the surface of the polytetrafluoroethylene (PTFE) film to obtain a modified polytetrafluoroethylene (PTFE) film as a negative friction material;
[0019] (3) A multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film and a modified polytetrafluoroethylene (PTFE) film are respectively attached to the upper surfaces of two copper foil electrodes, and a polyethylene terephthalate (PET) film is respectively attached to the lower surfaces of the copper foil electrodes. Then, the multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film and the modified polytetrafluoroethylene (PTFE) film are placed parallel to each other to obtain a friction nanogenerator (MTP-TENG).
[0020] The method for preparing a high-performance self-powered NO2 sensor based on a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material according to the present invention comprises the following steps:
[0021] The two gold electrode ends of the planar flexible NO2 gas sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive materials were connected to the positive and negative friction materials of the triboelectric nanogenerator (MTP-TENG) respectively, to obtain a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive materials.
[0022] The high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material of the present invention has the following advantages:
[0023] (1) Nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive materials were prepared by a simple hydrothermal method, annealing treatment and subsequent NO2 activation treatment. The method is simple and low-cost;
[0024] (2) The unique porous fibrous core-shell structure, effective nitrogen doping, and the resulting reconstruction of the surface electronic state of the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material enhance the NO2 adsorption capacity and charge transfer ability, thus achieving excellent NO2 sensing performance at room temperature;
[0025] (3) By integrating the N-MOF-In2O3 flexible sensor with the MTP-TENG, a self-powered flexible NO2 sensor device was realized, which converted the resistance signal into a voltage signal, improved the sensitivity of the sensor and shortened the response time;
[0026] (4) The commercially available planar flexible sensor has simple device processing, low cost, small size, and is suitable for mass production; it provides an effective strategy for high-performance, self-powered NO2 detection at room temperature, which is conducive to the development of portable gas-sensing devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1: A schematic diagram of the structure of a high-performance self-powered NO2 sensor based on a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material according to the present invention;
[0028] The names of the parts are: friction nanogenerator 1, planar flexible NO2 sensor 2, sensitive material 3, Keithley DMM6500 digital multimeter 4 (connected between the finger electrodes of the sensor, used to measure the voltage signal between the finger electrodes of the sensor in the air and under different NO2 concentrations);
[0029] Figure 2 :In the present invention Figure 2 (a) and Figure 2 (b) SEM photos of the MOF-derived In2O3 core-shell fiber structure sensitive material (MOF-In2O3) prepared in Comparative Example 2 and the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3) prepared in Example 1; Figure 2 (c) and Figure 2 (d) TEM morphology photos of the MOF-derived In2O3 core-shell fiber structure sensitive material (MOF-In2O3) prepared in Comparative Example 2 and the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3) prepared in Example 1; Figure 2 (e) and Figure 2 (f) HRTEM photos of the MOF-derived In2O3 core-shell fiber structure sensitive material (MOF-In2O3) prepared in Comparative Example 2 and the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3) prepared in Example 1. As can be seen from the figure, the material prepared in Comparative Example 2 presents a unique porous core-shell structure, with a wrinkled thin shell layer wrapped around the nanorod core; the wrinkled shell layer shows a highly porous and loose morphology, while the nanorod core is composed of dense nanoparticles; the SEM and TEM images of the material prepared in Example 1 clearly show that NO2 exposure has no effect on the core-shell structure. In addition, the lattice fringes of Comparative Example 2 and Example 1 have a lattice spacing of 0.293nm, which is consistent with the (222) plane of In2O3. Compared with the MOF-In2O3 core-shell fiber structure sensitive material (MOF-In2O3) prepared in Comparative Example 2, NO2 exposure had no effect on the core-shell structure of the nitrogen-doped MOF-In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3) prepared in Example 1. However, the wrinkled shell of N-MOF-In2O3 became rougher, with tighter and continuous folds, which may be due to the oxidizing nature of NO2.
[0030] Figure 3: The response recovery curves of the nitrogen-doped gas sensor prepared in Example 1 and Comparative Example 1 of the present invention correspond to Figure 3 (a) and Figure 3 (b); Compared with the response recovery time (1020s / 3933s) of the gas sensor in Comparative Example 1 to 1 ppm NO2, the response / recovery time (320s / 220s) of the sensor in Example 1 is faster.
[0031] Figure 4 : Column chart of the selectivity of the nitrogen-doped gas sensor prepared in Example 1 to different gases; The gas sensor of Example 1 was exposed to nitrogen dioxide, ammonia, xylene, methanol, hydrogen sulfide and sulfur dioxide, respectively. It can be seen that the response of the sensor to interfering gases (ammonia, xylene, methanol, hydrogen sulfide and sulfur dioxide) is negligible (sensitivity <2), indicating that it has a high selectivity for NO2 (the sensitivity of the sensor to 1 ppm nitrogen dioxide is 1460).
[0032] Figure 5 : The response recovery curves of the nitrogen-doped gas sensors prepared in Example 1 and Comparative Example 1 to 0.1-2 ppm and 1-5 ppm NO2 at room temperature correspond to Figure 5 (a) and Figure 5 (b); It can be seen that with the increase of NO2 concentration, the sensitivity of the sensor in Example 1 is significantly improved, showing a higher response than that in Comparative Example 1.
[0033] Figure 6 : The five cycle response recovery curves of the nitrogen-doped gas sensor prepared in Example 1 and Comparative Example 1 to 1ppm and 5ppm NO2 at room temperature correspond to Figure 6 (a) and Figure 6 (b) It can be seen that the response fluctuation of the sensor is within an acceptable range and has good repeatability.
[0034] Figure 7 : Schematic diagram of the working principle of the friction nanogenerator prepared by the present invention;
[0035] According to the triboelectric effect, when two triboelectric layers come into contact, a force ( Figure 7 -i), due to the difference in the triboelectric order between the two layers, electrons are transferred between the upper two layers. Multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film as a positive friction material is more likely to lose electrons and thus be positively charged (due to the difference in the triboelectric order between the two layers, electrons are transferred between the upper two layers), while the negative friction material polytetrafluoroethylene (PTFE) film is more likely to capture electrons and thus be negatively charged ( Figure 7-ii). When the pressure is removed and the two friction material layers are separated, the potential difference between the M-TPU film and the PTFE film drives the electrons in the copper foil (as the lower electrode) close to the PTFE film to move to the copper foil (as the upper electrode) close to the M-TPU film through the external circuit ( Figure 7 -iii). When the separation reaches the maximum, the charge in the copper foil (as the lower electrode) close to the PTFE film is equal to the charge in the PTFE film, and there is no electron flow in the external circuit ( Figure 7 -v). Subsequently, when force is applied again and the M-TPU film and the PTFE film are brought close together, the original electrostatic balance is broken, and the electrons in the copper foil (as the upper electrode) close to the M-TPU film move to the copper foil (as the lower electrode) close to the PTFE film through the external circuit, as shown in FIG. Figure 7 Finally, when the two friction layers are in full contact again, a new charge balance is achieved, resulting in no current signal in the external circuit ( Figure 7 -ii).
[0036] Figure 8 :Open circuit voltage and short circuit current curves of the triboelectric nanogenerator (MTP-TENG), corresponding to Figure 8 (a) and Figure 8 (b) The electrical performance of MTP-TENG was tested using a linear reciprocating machine with different vibration frequencies of 1 to 5 Hz. It can be seen that both the open circuit voltage and the short circuit current reached the maximum when the vibration frequency was 4 Hz. Therefore, in the experiment, the vibration frequency of the friction nanogenerator was set to 4 Hz. The open circuit voltage and short circuit current can be directly measured using a Keithley DMM6500 digital multimeter4.
[0037] When no power is supplied, when the sensor is placed in different concentrations of NO2, the resistance signal between the finger electrodes of the sensor will change, which is recorded using Fluke 8864A to establish a relationship curve between the resistance signal and the NO2 concentration; the present invention applies the open circuit voltage output by the friction nanogenerator between the finger electrodes of the sensor, and uses Keithley DMM6500 digital multimeter 4 to measure the voltage signal between the finger electrodes of the sensor, and the response is improved by 1.07 times and the response time is shortened by 28%. This is because the effective coupling between the sensor and the friction nanogenerator further enhances the charge transfer process, thereby improving the performance.
[0038] The open circuit voltage output by the friction nanogenerator will affect the voltage value between the sensor finger electrodes in the air and in the gas to be measured (the friction nanogenerator is equivalent to a power supply, and the sensor finger electrodes and the Keithley DMM6500 digital multimeter are connected in series and then connected to the power supply. The two have a certain resistance and will divide the voltage. If the power supply voltage increases, the voltage between the sensor finger electrodes will also increase. Therefore, the open circuit voltage output by the friction nanogenerator will affect the voltage value between the sensor finger electrodes in the air and in the gas to be measured), and the output voltage of the friction nanogenerator is affected by many factors, including the pressure applied to the friction nanogenerator. In the present invention, a linear reciprocating machine (voltage 24V, stroke 3.5 cm) is used to provide pressure for the friction nanogenerator. Different vibration frequencies of the linear reciprocating machine will affect the magnitude of the pressure.
[0039] Fig. 9 (a) is a curve showing the variation of the voltage between the interdigital electrodes of the self-powered NO2 sensor based on Example 2 in a wide range of NO2 concentrations from 0 ppb to 1 ppm (the voltages at 0.5 ppm and 1 ppm are approximately 1 V and 4 V, respectively), indicating that the device voltage increases significantly with the increase of NO2 concentration; Fig. 9 (b) is the dynamic response and recovery output voltage curve of the self-powered NO2 sensor to 1ppm NO2, indicating that the response / recovery time of the self-powered NO2 sensor based on Example 2 to 1ppm NO2 at room temperature is 230 / 200s. In addition, it can be seen that when the device of Example 2 is exposed to 1ppm NO2, the voltage signal changes rapidly, and the response reaches 1558 (0ppm is the initial voltage, and the response is (1ppm voltage) / (0ppm initial voltage)). Compared with the sensitivity of the resistance signal measured by the sensor (such as Figure 3 to Figure 6 ), after the sensor is combined with the friction nanogenerator, the response (such as Fig. 9 ) increased by 1.07 times and the response time was shortened by 28%.
[0040] Note: The sensitivity (response value) of the device is defined as the ratio of the resistance value between its two gold electrodes in the measured gas to the resistance value in the air. The response and recovery time is the time it takes for the sensor's resistance value to change to 90% of the total value after the gas environment in which the device is located is changed (from air to NO2 gas or from NO2 gas to air). Use a static test system for testing: place the device in a 1-liter gas cylinder, configure a certain concentration of the gas to be tested in the cylinder, observe and record its resistance change, and calculate the corresponding sensitivity value and response recovery time.
[0041] Traditional non-self-powered sensors rely on power supplies, which are often bulky. In this application, a triboelectric nanogenerator (MTP-TENG) provides a promising approach to convert mechanical energy from the surrounding environment into electrical energy, facilitating the development of self-powered nitrogen dioxide sensors and eliminating the reliance on traditional power supplies. DETAILED DESCRIPTION
[0042] Embodiment 1:
[0043] (1) 0.598 g In(NO3)3·4.5H2O and 0.234 g terephthalic acid were dissolved in 20 mL dimethylformamide (DMF) solution and stirred for 30 min to obtain a homogeneous solution;
[0044] (2) adding the uniform solution obtained in step (1) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing the autoclave well and maintaining the autoclave at 125° C. for 5 hours;
[0045] (3) After the autoclave is naturally cooled to room temperature, the reaction product is taken out, the precipitate is collected by centrifugation, and the precipitate is washed alternately with water and ethanol for 6 times, and then the precipitate is dried at 80°C for 12 hours to obtain a solid powder; the obtained solid powder is transferred to a porcelain boat and placed in a muffle furnace, and calcined at 600°C in air for 2 hours (heating rate 5.0°C / min), thereby obtaining a MOF-derived In2O3 core-shell fiber structure sensitive material;
[0046] (4) Take 15 mg of the MOF-derived In2O3 core-shell fiber structure sensitive material obtained in step (3) in an agate mortar, drop 200 μL of ethanol, mix thoroughly and grind into a paste, then dip an appropriate amount of the paste and evenly coat it on a polyimide (PI) substrate with a gold (Au) interdigitated electrode on the surface to form a 20 μm thick sensitive material layer, and make the sensitive material completely cover the surface of the polyimide (PI) substrate and the gold (Au) interdigitated electrode;
[0047] (5) drying the PI substrate coated with the sensitive material obtained in step (4) in air at 70° C. for 2 hours, thereby preparing a planar flexible NO2 gas sensor of MOF-derived In2O3 core-shell fiber structure sensitive material;
[0048] (6) Exposing the MOF-derived In2O3 core-shell fiber structure sensitive material obtained in step (5) to 5 ppm NO2 for 2 hours to obtain a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material (N-MOF-In2O3), thereby preparing a planar flexible NO2 gas sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material.
[0049] Embodiment 2:
[0050] (1) Preparation of multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU): 7.176 g of thermoplastic polyurethane (TPU) particles were added to 40 mL of dimethylformamide (DMF) solution, followed by the addition of 1.0 g of multi-walled carbon nanotubes (MWCNT), and the mixture was kept at 70° C. for 12 hours; 30 g of sodium chloride (NaCl) was then added, and the mixture was kept at 70° C. for 6 hours; the resulting product was then dried at 70° C. for 5 hours, and then dissolved in 60° C. water for 1.0 hour to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) as a positive friction material, and then placed in a polytetrafluoroethylene mold for drying to obtain a 3 mm thick multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) film;
[0051] (2) Preparation of modified polytetrafluoroethylene (PTFE) film: using P1000 grade sandpaper to uniformly rub the surface of the polytetrafluoroethylene (PTFE) film to obtain a modified polytetrafluoroethylene (PTFE) film as a negative friction material;
[0052] (3) attaching multi-walled carbon nanotube-modified thermoplastic polyurethane (M-TPU) and modified polytetrafluoroethylene (PTFE) films to the surfaces of two copper foil electrodes, respectively, and attaching polyethylene terephthalate (PET) films under the copper foil electrodes, respectively, to obtain a friction nanogenerator (MTP-TENG) (a pressing operation is required during the power generation test, with a pressure of about 30 N; the pressure is generated by the vibration of the linear reciprocating machine);
[0053] (4) The two gold electrode ends of the planar flexible NO2 gas sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material prepared in Example 1 were respectively connected to the positive and negative friction materials of the friction nanogenerator (MTP-TENG) to obtain a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material.
[0054] Comparative Example 1:
[0055] (1) Take 15 mg of commercial indium oxide sensitive material in an agate mortar, drop 200 μL of ethanol, mix thoroughly and grind into a paste, then take an appropriate amount of the paste and evenly coat it on a polyimide (PI) substrate with gold (Au) interdigitated electrodes on the surface to form a 20 μm thick sensitive material layer, and make the sensitive material completely cover the surface of the polyimide (PI) substrate and the gold (Au) interdigitated electrodes;
[0056] (2) drying the PI substrate coated with the sensitive material obtained in step (1) in air at 70° C. for 2 hours, thereby preparing a planar flexible NO2 gas sensor based on commercial indium oxide sensitive material;
[0057] (3) Exposing the commercial indium oxide sensitive material obtained in step (2) to 5 ppm NO2 for 2 hours to obtain a nitrogen-doped commercial indium oxide sensitive material, thereby preparing a planar flexible NO2 gas sensor based on the nitrogen-doped commercial indium oxide sensitive material.
[0058] Comparative Example 2:
[0059] (1) 0.598 g In(NO3)3·4.5H2O and 0.234 g terephthalic acid were dissolved in 20 mL dimethylformamide (DMF) solution and stirred for 30 min to obtain a homogeneous solution;
[0060] (2) adding the uniform solution obtained in step (1) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing the autoclave well and maintaining the autoclave at 125° C. for 5 hours;
[0061] (3) After the autoclave is naturally cooled to room temperature, the precipitate is collected by centrifugation, and the precipitate is washed alternately with water and ethanol for 6 times, and then the obtained product is dried at 80°C for 12 hours to obtain a solid powder; the obtained solid powder is transferred to a porcelain boat and placed in a muffle furnace, and calcined at 600°C in air for 2 hours (heating rate 5.0°C / min), thereby obtaining a MOF-derived In2O3 core-shell fiber structure sensitive material;
[0062] (4) Take 15 mg of the MOF-derived In2O3 core-shell fiber structure sensitive material obtained in step (3) in an agate mortar, drop 200 μL of ethanol, mix thoroughly and grind into a paste, then dip an appropriate amount of the paste and evenly coat it on a polyimide (PI) substrate with a gold (Au) interdigitated electrode on the surface to form a 20 μm thick sensitive material layer, and make the sensitive material completely cover the surface of the polyimide (PI) substrate and the gold (Au) interdigitated electrode;
[0063] (5) The PI substrate coated with the sensitive material obtained in step (4) is dried in air at 70° C. for 2 hours to prepare a planar flexible NO2 gas sensor of MOF-derived In2O3 core-shell fiber structure sensitive material (MOF-In2O3).
Claims
1. A method for preparing a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material, characterized in that: The two gold electrode ends of the planar flexible NO2 gas sensor based on the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material are respectively connected to the positive and negative friction materials of the friction nanogenerator to obtain the high-performance self-powered NO2 sensor based on the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material.
2. A method for preparing a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material as claimed in claim 1, characterized in that: The planar flexible NO2 gas sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material was prepared by the following steps: (1) 10-20 mg of MOF-derived In2O3 core-shell fiber structure sensitive material is placed in an agate mortar, 150-200 μl of ethanol is added, the mixture is fully mixed and ground into a paste; the paste is then dipped and evenly coated on a polyimide substrate with a gold interdigital electrode on the surface to form a 15-30 μm thick sensitive material layer, and the sensitive material layer completely covers the surface of the polyimide substrate and the gold interdigital electrode; (2) The PI substrate coated with the sensitive material obtained in step (1) is dried in air at 60 to 80° C. for 1.5 to 3.0 hours, thereby preparing a planar flexible NO2 gas sensor of MOF-derived In2O3 core-shell fiber structure sensitive material. (3) Exposing the MOF-derived In2O3 core-shell fiber structure sensitive material in step (2) to 3-8 ppm NO2 for 1-3 hours to obtain a nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material, thereby preparing a planar flexible NO2 gas sensor based on the nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material.
3. A method for preparing a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material as claimed in claim 2, characterized in that: The number of pairs of gold interdigital electrodes is 12 to 18 pairs, and the distance between each pair of electrodes is 40 to 60 μm; the size of the polyimide substrate is (8 to 12 mm)×(8 to 12) mm.
4. A method for preparing a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material as claimed in claim 2, characterized in that: The MOF-derived In2O3 core-shell fiber structure sensitive material was prepared by the following steps: (1) Dissolve 0.50-0.65 g In(NO3)3·4.5H2O and 0.20-0.30 g terephthalic acid in 15-25 mL dimethylformamide solution and stir for 25-35 min to obtain a uniform solution; (2) adding the uniform solution obtained in step (1) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing the autoclave well and maintaining the autoclave at 110 to 140° C. for 3 to 7 hours; (3) After the autoclave is naturally cooled to room temperature, the reaction product is taken out, the precipitate is collected by centrifugation, and the precipitate is washed alternately with water and ethanol for 5 to 8 times, the precipitate is dried at 70 to 90° C. for 10 to 20 hours to obtain a solid powder, and the solid powder is calcined in air at 400 to 600° C. for 1.5 to 3.0 hours to obtain a MOF-derived In2O3 core-shell fiber structure sensitive material.
5. A method for preparing a high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material as claimed in claim 1, characterized in that: The friction nanogenerator is prepared by the following steps: (1) Preparation of multi-walled carbon nanotube-modified thermoplastic polyurethane film: 6-9 g of thermoplastic polyurethane particles are added to 40 mL of dimethylformamide solution, followed by 0.5-1.5 g of multi-walled carbon nanotubes, and the mixture is kept at 60-80° C. for 10-15 hours; 23-35 g of sodium chloride is then added, and the mixture is kept at 60-80° C. for 5-8 hours; the resulting product is then dried at 60-80° C. for 3-6 hours, and then dissolved in 50-70° C. water for 0.5-1.5 hours to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane as a positive friction material, and then placed in a polytetrafluoroethylene mold and dried to obtain a multi-walled carbon nanotube-modified thermoplastic polyurethane film with a thickness of 2-5 mm; (2) Preparation of modified polytetrafluoroethylene film: using P1000 grade sandpaper to uniformly rub the surface of the polytetrafluoroethylene film to obtain a modified polytetrafluoroethylene film as a negative friction material; (3) A thermoplastic polyurethane film modified by multi-walled carbon nanotubes and a modified polytetrafluoroethylene film are respectively attached to the upper surfaces of two copper foil electrodes, and a polyethylene terephthalate film is respectively attached to the lower surfaces of the copper foil electrodes, and then the thermoplastic polyurethane film modified by multi-walled carbon nanotubes and the modified polytetrafluoroethylene film are placed parallel to each other, thereby obtaining a friction nanogenerator.
6. A high-performance self-powered NO2 sensor based on nitrogen-doped MOF-derived In2O3 core-shell fiber structure sensitive material, characterized by: The method is prepared by any one of claims 1 to 5.
Citation Information
Cited By
Self-powered nitrogen dioxide sensing system with excellent performance
CN120161089A
A self-powered nitrogen dioxide sensing system with excellent performance
CN120161089B